Contemporary wedding crafts : over 40 stylish projects for the modern bride - 20160731 frey50; Fox-Proverbs, Jennifer (Newton Abbot : David & Charles, 2010)
Shows how to make wedding invitations, favors, jewelery, decorations, sweet treats, centerpieces and gifts. It is ideal for the novice crafter, with lots of clear step-by-step photography and explanation, plus tips for producing multiples such as invitations.
Includes index.
Keywords: Wedding decorations; Weddings -- Planning